A Biomimic Reconstituted High Density Lipoprotein Nanosystem for Enhanced VEGF Gene Therapy of Myocardial Ischemia. (2nd April 2015) - Sun, Xiaotian; Wang, Wenshuo; Huang, Jiechun; Lai, Hao; Guo, Changfa; Wang, Chunsheng
Abstract : A biomimic reconstituted high density lipoprotein (rHDL) based system, rHDL/Stearic-PEI/VEGF complexes, was fabricated as an advanced nanovector for delivering VEGF plasmid. Here, Stearic-PEI was utilized to effectively condense VEGF plasmid and to incorporate the plasmid into rHDL. The rHDL/Stearic-PEI/VEGF complexes with diameter under 100 nm and neutral surface charge demonstrated enhanced stability under the presence of bovine serum albumin. Moreover, in vitro cytotoxicity and transfection assays on H9C2 cells further revealed their superiority, as they displayed lower cytotoxicity with much higher transfection efficiency when compared to PEI 10K/VEGF and Lipos/Stearic-PEI/VEGF complexes. In addition, in vivo investigation on ischemia/reperfusion rat model implied that rHDL/Stearic-PEI/VEGF complexes possessed high transgene capacity and strong therapeutic activity. These findings indicated that rHDL/Stearic-PEI/VEGF complexes could be an ideal gene delivery system for enhanced VEGF gene therapy of myocardial ischemia, which might be a new promising strategy for effective myocardial ischemia treatment.